2010
DOI: 10.1074/jbc.m109.081166
|View full text |Cite
|
Sign up to set email alerts
|

UTP Controls Cell Surface Distribution and Vasomotor Activity of the Human P2Y2 Receptor through an Epidermal Growth Factor Receptor-transregulated Mechanism

Abstract: Extracellular nucleotides transmit signals into the cells through the P2 family of cell surface receptors. These receptors are amply expressed in human blood vessels and participate in vascular tone control; however, their signaling mechanisms remain unknown. Here we show that in smooth muscle cells of isolated human chorionic arteries, the activation of the P2Y 2 receptor (P2Y 2 R) induces not only its partition into membrane rafts but also its rapid internalization. Cholesterol depletion with methyl-␤-cyclod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…Use of BV-2 cells, a Cav-1 devoid microglial cell line expressing P2Y 2 Rs, substantiates this finding, because P2Y 2 R was found to reside in high density membrane fractions (Fig. 2) (67).…”
Section: Discussionsupporting
confidence: 62%
“…Use of BV-2 cells, a Cav-1 devoid microglial cell line expressing P2Y 2 Rs, substantiates this finding, because P2Y 2 R was found to reside in high density membrane fractions (Fig. 2) (67).…”
Section: Discussionsupporting
confidence: 62%
“…There, the use of AG1478, a selective and potent inhibitor of the EGFR tyrosine kinase activity, not only blocked the UTP-induced vasomotor activity but also abrogated both RhoA and Rac1 activation, the P2Y 2 receptor association with membrane rafts, and its internalization. These results reveal an unsuspected functional interplay that controls both the membrane distribution and the vasomotor activity of the P2Y 2 receptor in intact human blood vessels [88].…”
Section: P2 Receptors and Rtksmentioning
confidence: 95%
“…Various signal transduction pathways (which are associated with vasoconstriction) activated by P2Y receptor stimulation have been proposed, including MAPK, Rho A/Rho kinase, and EGF receptor (EGFR) transactivation (47,54). Moreover, several reports have demonstrated that these signal transduction pathways are altered in various animal models, including mineralocorticoid hypertension (5,18,19,59).…”
Section: Discussionmentioning
confidence: 99%